2020
DOI: 10.26714/jkj.8.3.2020.273-278
|View full text |Cite
|
Sign up to set email alerts
|

Factors on Quality of Life in Scizofrenia Patients

Abstract: Schizophrenia is a mental disorder characterized by symptoms such as hallucinations and delusions. These symptoms can affect the quality of life in people with schizophrenia. From the data of Tanjung Paku Health Center, which suffers from schizophrenia as many as 46 people. The purpose of this study was to describe the life quality factors of schizophrenics in the working area of Tanjung Paku health center in Solok city in 2019. The purpose of this study was to describe the life quality factors of schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Gejala-gejala skizofrenia dapat dibagi menjadi 2 kelompok yaitu: gejala primer (gangguang proses pikir, gangguan efek dan emosi, gangguan kemauan, gejala psikomotor) dan gejala sekunder (waham dan halusinasi) Skizofrenia merupakan gangguan yang berlangsung selama minimal 1 bulan gejala fase aktif. Dibanding dengan gangguan mental yang lain, skizofrenia bersifat kronis dan melemahkan, bagi individu yang pernah mengidap skizofrenia dan pernah dirawat, maka kemungkinan kambuh sekitar 50-80% (Afconneri, & Puspita, 2020).…”
Section: Pembahasanunclassified
“…Gejala-gejala skizofrenia dapat dibagi menjadi 2 kelompok yaitu: gejala primer (gangguang proses pikir, gangguan efek dan emosi, gangguan kemauan, gejala psikomotor) dan gejala sekunder (waham dan halusinasi) Skizofrenia merupakan gangguan yang berlangsung selama minimal 1 bulan gejala fase aktif. Dibanding dengan gangguan mental yang lain, skizofrenia bersifat kronis dan melemahkan, bagi individu yang pernah mengidap skizofrenia dan pernah dirawat, maka kemungkinan kambuh sekitar 50-80% (Afconneri, & Puspita, 2020).…”
Section: Pembahasanunclassified
“…Another study in Nigeria found that the average quality of life for ODS was low, namely 76.19 (SD=10.34) (Adelufosi, Ogunwale, Abayomi, & Mosanya, 2013). The impact on quality of life and having a standard of living that is significantly worse than other people includes several things including, physical health, mental health, level of dependence, individual beliefs and relationships with the surrounding environment (Afconneri & Puspita, 2020).…”
Section: Introductionmentioning
confidence: 99%